Terminal Kalibaru sebagai Solusi Mengatasi Kemacetan Bongkar Muat Peti Kemas di Pelabuhan Tanjung Priok Jakarta, 2011-2016 - P. Padliansyah; Sutejo K. Widodo; Endang Susilowati (Indonesian Historical Studies, 2019)
This study argues that container loading and unloading congestion at Tanjung Priok Port is caused by long dwelling time due to the limited capacity of existing container terminals. Therefore, the Kalibaru Terminal was built to overcome this problem. The research objective is to look at the planning, construction, and operation of the Kalibaru Terminal. This study uses historical methods consisting of heuristics, source criticism, interpretation, and historiography. The results of this study indicate that the construction of the Kalibaru Terminal is a superior project of government and private cooperation so that it must go through an international tender. The development of Kalibaru Terminal aims to increase productivity and accelerate economic growth. The existence of the Kalibaru Terminal also caused the flow of goods to run smoothly and decrease in dwelling time from eight to three days.